Stress and Skin Disorders : Basic and Clinical Aspects - França, Katlein; Jafferany, Mohammad (Springer International Publishing : Imprint: Springer, 2017)
Dermatological conditions are intimately related to stress. Stress can affect, reveal or even exacerbate a number of skin disorders, including alopecia, seborrheic dermatitis, psoriasis, atopic dermatitis, pruritus, herpes, lichen planus, rosacea and urticarial. On the other hand, the skin disease itself could induce a secondary stress for the patient, influencing his or her quality of life. There is increasing evidence that stress influences disease processes and contributes to inflammation through the modulating hypothalamicpituitary- adrenal axis - releasing neuropeptides, neurotrophins, lymphokines and other chemical mediators from nerve endings to dermal cells. This is one of the first books published on this topic, focusing more on the basic science aspects of stress in dermatopathology (oxidants, antioxidants, and oxidative injury in dermatopathology, dermatopharmacology, and dermatotoxicology.) Most Psychodermatology texts adopt a practical approach to identify all types of Psychodermatology disorders, focusing on clinical treatment. This concise title offers a comprehensive and didactic approach to skin diseases caused or exacerbated by stress, as well as covers the immunology, role and effect of stress on skin disease, and quality of life in dermatology. In the current programs of medical residency in dermatology, little is taught about the relationship between stress and skin diseases and this book is an important tool for young dermatologists and psychodermatologists in training. .